Utility of local anesthesia for open carpal tunnel release in patients with psychiatric diagnoses. (March 2020) - Ayyala, Haripriya S.; Castel, Nikki; Mohamed, Omar M.; Xue, Erica Y.; Oleck, Nicholas C.; Lee, Edward S.
Abstract: Purpose: Carpal tunnel release, one of the most commonly performed procedures in Veterans Affairs (VA) medical centers, is often performed under local anesthesia alone. In this patient population, there is an increased prevalence of psychiatric disorders. Our hypothesis is that there is no difference in operating time, request for sedation, or complications in the veteran population with or without a recognized psychiatric history. Methods: A retrospective cohort study was performed at a VA medical center from January 2013 to January 2017 by the senior surgeon (E.S.L). Patients were divided into two groups: patients with no known psychiatric history ( n = =33) and patients with an active psychiatric diagnosis ( n = =25), including post-traumatic stress disorder, anxiety disorder, bipolar disorder, depression, substance abuse, or panic disorder. Primary endpoints included operation time, time in operating room, request for sedation, and complication rates. Results: Fifty-nine percent of patients successfully underwent wide-awake hand surgery, while 41% requested sedation. Patients with no known psychiatric history had a 45.5% rate of requesting sedation compared to 36% in those with a psychiatric diagnosis. No patients converted from wide-awake surgery to sedation. There was no statistically significant difference in operation time, time in the operating room, need for sedation, or complication rate between all groups. Conclusions: Wide-awake hand surgery is an excellent technique that can be safely used in patients with a history of psychiatric illness. Without the need for monitored anesthesia care, the cost for carpal tunnel releases done in military medical centers could decrease dramatically. Type of Study: Prognostic Level of Evidence: Level II